IMPLEMENTASI UNPLUGGED CODING GAMES DALAM MENINGKATKAN KEMAMPUAN BERPIKIR ANAK USIA DINI - Hutabarat, Eka Putri Sulistia; Rachmy Diana, Raden; Sri Rezeki, Afriya (Jurnal Muara Pendidikan, 2025)
Getting to know children in technology, especially computers, is very important to do as a provision for children to face future challenges and improve their thingking skill. The learning can be done through a game and without using technological device or what is called unplugged coding games. This study aims to find out how the implementation of unplugged coding games in improving thingking skills is carried out. The method used is qualitative method with a descriptive approach through a type of field research conducted at PAUD Harapan Ummat Medan Polonia with data sources 1 Principal, 2 teachers and 15 children from the mecca class. The results of the study found that in the implementation of unplugged coding games activities were included in the opening activities, core activities, and closing activities. Unplugged coding games activities carried out were in form of tradisional games of engklek, tansoa (sholeh-sholeha children’s ladder), origami, playing loosepart-based puzzels, combining dots, coloring pictures with codes, filling in missing numbers and solving secret codes using numbers and letters. By implementing unplugged coding games in learning, it can improve children’s thingking skill so that children are able to show experiencing failure, showing ideas, recognizing and solving problems.